Retro Melbourne : 20 postcards - Mitchell, Fred ([Chatswood, NSW] : New Holland Publishers, 2015)
Discover your inner artist with these 20 detachable postcards for people of all ages to complete and share with friends and family.
Postcard book.
"Take a walk down memory lane with these retro Melbourne postcards" --Back cover.
Keywords: Cities and towns -- Victoria -- Melbourne -- History -- 20th century; Cities and towns -- Victoria -- Melbourne -- Pictorial works; Melbourne (Vic.) -- Buildings, structures, etc -- History -- 20th century; Melbourne (Vic.) -- Buildings, structures, etc -- Pictorial works; Australian